2016
DOI: 10.1002/prep.201600091
|View full text |Cite
|
Sign up to set email alerts
|

Burning Rates and Thermal Behavior of Bistetrazole Containing Gun Propellants

Abstract: The influence of two selected bistetrazoles, 5,5′‐bis(1H‐tetrazolyl)‐amine (BTA) and 5,5′‐hydrazinebistetrazole (HBT), on the combustion behavior of a typical triple‐base propellant was investigated. Seven propellant formulations, one reference and six others incorporating 5 %, 15 %, and 25 % of either HBT or BTA compounds, respectively, were mixed and extruded into a cylindrical, no perforations, geometry. The resulting propellants showed high burning rates, up to 93 % higher than the reference formulation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
11
1
Order By: Relevance
“…In addition to the increased burning rates, there is also a significant change in the linear burn rate coefficients and pressure exponents. This is different from the previously re-ported burning rate law parameters for propellants containing BTA and HBT where an increase in pressure exponent was observed rather than a decrease [14]. This agrees with the statement that mixtures of nitrogen-rich materials with other energetics can show an increase in pressure exponent and a decrease in linear burn rate coefficient followed by the reverse when the nitrogen-rich content increases.…”
Section: Performancecontrasting
confidence: 67%
See 4 more Smart Citations
“…In addition to the increased burning rates, there is also a significant change in the linear burn rate coefficients and pressure exponents. This is different from the previously re-ported burning rate law parameters for propellants containing BTA and HBT where an increase in pressure exponent was observed rather than a decrease [14]. This agrees with the statement that mixtures of nitrogen-rich materials with other energetics can show an increase in pressure exponent and a decrease in linear burn rate coefficient followed by the reverse when the nitrogen-rich content increases.…”
Section: Performancecontrasting
confidence: 67%
“…It goes without saying that new propellants designed to have lower erosivity should also provide equal or better performance than the propellants they are designed to replace. The positive effects of nitrogen-rich materials on the burning rate of propellants have already been demonstrated by Mason et al and Lavoie et al [13,14]. It was shown that in certain cases, despite the lower flame temperature, the experimental maximum pressure observed for nitrogen-rich propellants in a closed vessel was equivalent to that of formulations that did not incorporate nitrogen-rich materials, an indication that the same performance level is attainable [14].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations